The Women on the Porch - Gordon, Caroline (J.S. Sanders, 1993)
One of the most remarkable novels every written by an American woman about women. First published in 1943, the story follows a woman’s flight from Manhattan and her unfaithful husband to her rural ancestral home. Southern Classics Series.